FC 054FUNCTIONAL SODIUM MAGNETIC RESONANCE IMAGING OF THE HUMAN KIDNEY. (29th May 2021) - Lemoine, Sandrine; Akbari, Alireza; Marcus, Taylor; McIntyre, Christopher
Abstract: Background and Aims: Maintenance of a cortico-medullary concentration gradient (CMG) required for urine concentration, is one of most important tubular function. However, we are lacking of functional tubular parameters to explore this function. The only tool available to assess it currently, is urinary osmolarity that is an indirect and nonspecific maker of CMG. In this study, we explore the ability of 23 NaMRI in measuring 1) the dynamics of CMG for the first time compared to urinary osmolarity after a water load 2) the CMG in kidney disease. Method: We conducted an exploratory pilot study for 10 healthy controls with water load then 5 cardiorenal patients with kidney disease. 1) Healthy controls were asked to be fasting since midnight. Urines sample were collected to measure fasting osmolarity and a first MRIscan were performed to acquire baseline anatomical and sodium images. Once the baseline was completed, healthy participants were asked to ingest water (15 mL/kg) within 15 minutes. Four subsequent sodium pictures were acquired an hour after water ingestion. Urine samples were obtained after each sodium acquisition every 15 min during one hours. 2) Cardiorenal patients underwent an MRI scan, provided a spot urine sample and have blood work collected. All MR experiments were carried out on a GE MR750 3T (GE Healthcare, WI). A custom-built two-loop (18cm in diameter) butterfly radiofrequency surface coil tuned for 23 Na frequency (33.786 MHz) was used to acquire renal 23 Na images. Results: Mean age of the 10 healthy controls was 41.8 ± 15.3 years, mean body mass index (BMI) was 24.3 ± 3.8 kg/m 2 . Mean water intake was 1092 ± 233 mL, total water excreted was 1250 ± 301 mL . Mean age of the 5 cardiorenal patients was 76.6 ± 12.2 years, mean BMI was 28.1 ± 6.9 kg/m 2 . eGFR was 54 ± 37 mL/min/1.73m 2 . Urinary osmolarity was 498 ± 145 mosm/L and medulla/cortex ratio was 1.35 ± 0.11. Sodium imaging was successfully acquired in all volunteers. In the morning fasting, medulla/cortex ratio was 1.55 ± 0.11 regarding to a urinary osmolarity to 814 ± 121 mosm/L. Mean ± SD fasting urinary osmolarity dropped significantly to 73 ± 14 mosm/L for maximal dilution, p=0.001. Mean medulla/cortex ratio dropped significantly to 1.31 ± 0.09 mosm/L for maximal dilution, p=0.002. Figure 1 displays changes of 23 NaMRI pictures before (A) then 1h (B), 1H15 (C), 1h30 (D) and 1h45 (E) after a water load. Urinary osmolarity and medulla/cortex ratio are significantly correlated, r=0.54, p=0.0001. We measured corticomedullary gradient in cardiorenal patient with different level of eGFR to show the ability and feasibility to measure this gradient in pathological settings. We were able to measure medulla/cortex ratio in patients with CKD with a mean SNR of 20.45 ± 9.45. Conclusion: We explored CMG dynamically every 15 min and we were able to discriminate significant changes after a water load. We were also able to provide efficient 23 NaMRI pictures in cardiorenal patients with kidney disease. CMG exploration would provide a relevant assessment of tubular dysfunction independently of glomerular alteration and thus could be of prognostic value.